Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/2473011416s00297
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Protease-Activated Receptors 1 And 4 In Human Platelet Activation And Inflammation

Abstract: Category: Basic Sciences/Biologics Introduction/Purpose: Tendon injuries occur frequently and cost billions of health care dollars annually. Recently, there has been an increase in the use of platelet-rich plasma (PRP) to treat tendon injuries. However, the efficacy of PRP treatment is controversial due to inconsistent results from human clinical trials. It is thought that variations in PRP preparation contribute to these inconsistencies. Specifically, platelets in PRP contain pro-angiogenic (e.g. VEGF) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PAR1 combines with thrombin to induce thrombosis. Thrombin binding to PAR1 on platelets induces platelet activation and strengthens platelet adhesion in order to promote the aggregation of platelets and thus cause thrombosis (36,37). Another study demonstrated that PR3 induced platelets to change shape via the Rho/Rho kinase and Ca 2+ signaling pathways (38).…”
Section: Discussionmentioning
confidence: 99%
“…PAR1 combines with thrombin to induce thrombosis. Thrombin binding to PAR1 on platelets induces platelet activation and strengthens platelet adhesion in order to promote the aggregation of platelets and thus cause thrombosis (36,37). Another study demonstrated that PR3 induced platelets to change shape via the Rho/Rho kinase and Ca 2+ signaling pathways (38).…”
Section: Discussionmentioning
confidence: 99%